Prospects of Development of Silk Road Economic Belt and New Opportunities of Economic Growth - ZHARTAY, Zhanibek; KHUSSAINOVA, Zhibek; ABAUOVA, Gulzhan; AMANZHOLOVA, Botagoz (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).35, 2018)
The article analyzes the genesis and the potential of the Chinese Program ‘Silk Road Economic Belt’, as well as limiting factors and perspectives of further development. The article explains the dialectical relationship and the dualistic nature of regionalization. The author's hypothesis is based on the idea that the dominant purpose of regional integration as a model of the active participation of the consolidated group of countries in the region in the globalization process of stratification of the world is the desire of the participating countries to take a higher position (stratum) in the global hierarchy, and eliminate the possibility of a drift towards the periphery. The author used the concept of methodological possibilities of the ‘theory of the new regionalism’ and geopolitical doctrine of Eurasianism to explain the background and development of the capacity of the Silk Road Economic Belt, that allow to evaluate the quantitative and qualitative parameters of the Silk Road Economic Belt functioning, limiting factors and perspectives for its further development.